Empowering Higher-Order Thinking Skills: STEM-PjBL with Jambi (Malay) Local Content for Madrasah Tsanawiyah Students - Haerul Pathoni; Alrizal Alrizal; Aulia Sanova; Louisiana Muliawati (STAI Hubbulwathan Duri, 2025)
This study investigates the effectiveness of a Project-Based Learning (PjBL) model integrated with STEM and infused with local Jambi (Malay) cultural content in enhancing students' Higher Order Thinking Skills (HOTS) in science education at MTS Bina Insan. An experimental design using a non-equivalent control group was employed, involving two classes—experimental and control—each comprising 13 students. The experimental group received instruction through the PjBL-STEM model incorporating local content, while the control group followed traditional methods. Both groups underwent pre-tests and post-tests. Data were analyzed using normality tests and independent t-tests. Pre-test and post-test data met the assumption of normality (p 0.05). An independent t-test indicated a statistically significant difference between the post-test scores of the experimental and control groups (p 0.005), supporting the alternative hypothesis. The results suggest that the PjBL-STEM model, when contextualized with local Jambi culture, significantly enhances students' HOTS. The integration of cultural elements made the learning process more relevant and engaging, supporting deeper cognitive engagement. The study demonstrates that integrating local cultural content into STEM-based PjBL strategies effectively improves students’ higher-order thinking skills. This finding highlights the value of culturally responsive pedagogy in creating meaningful and contextually appropriate science education.